Phosphatidylcholine deficiency upregulates enzymes of triacylglycerol metabolism in CHO cells - Caviglia, Jorge Matías (2004)
We studied the regulation of triacylglycerol (TAG) metabolism by phosphatidylcholine (PC) in CHO MT58 cells, which are deficient in PC synthesis because of a temperature-sensitive CTP:phosphocholine cytidylyltransferase. At the permissive growth temperature (34°C), these cells contained 49% less TAG and 30% less PC than wild-type CHO K1 cells. Treatment with dipalmitoylphosphatidylcholine normalized both the PC and TAG levels. Despite low TAG levels, the incorporation of [14C] oleate into TAG was increased in CHO MT58 cells. The in vitro de novo synthesis of TAG and the activity of diacylglycerol acyltransferase were 90% and 34% higher, respectively. Two other key enzyme activities in TAG synthesis, acyl-CoA synthetase and mitochondrial glycerol-3-phosphate acyltransferase (GPAT), increased by 48% and 2-fold, respectively, and mitochondrial GPAT mRNA increased by ∼4-fold. Additionally, TAG hydrolysis was accelerated in CHO MT58 cells, and in vitro lipolytic activity increased by 68%. These studies suggest that a homeostatic mechanism increases TAG synthesis and recycling in response to PC deficiency. TAG recycling produces diacylglycerol and fatty acids that can be substrates for de novo PC synthesis and for lysophosphatidylcholine (lysoPC) acylation. In CHO MT58 cells, in which de novo PC synthesis is blocked, lysoPC acylation with fatty acid originating from TAG may represent the main pathway for generating PC.